2022
DOI: 10.3389/fbioe.2022.800748
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physiological Tendon Substrate Stiffness Have Moderate Effects on Tendon-Derived Cell Growth and Immune Cell Activation

Abstract: Tendinopathy is characterised by pathological changes in tendon matrix composition, architecture, and stiffness, alterations in tendon resident cell characteristics, and fibrosis, with inflammation also emerging as an important factor in tendinopathy progression. The sequence of pathological changes in tendinopathy and the cellular effects of the deteriorating matrix are largely unknown. This study investigated the effects of substrate stiffness on tendon-derived cells (TDCs) and THP-1 macrophages using PDMS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Degenerative tendinopathy, on the other hand, represents a noninflammatory proliferative cell and matrix response with increases in type III collagen production, extracellular matrix disorganization, and cell death, which can manifest as increased tissue stiffness. 43 In studies of the axial spine, it was observed that in certain cases there was no notable variance in tissue stiffness within the trapezius muscle or sciatic nerve when comparing patients with pathology to healthy control participants. 22,23 However, several studies indicated that comparing side-to-side evaluations of Young's modulus or SWV in the same individual, between the symptomatic and asymptomatic side, will provide helpful diagnostic information, as noted in comparison of sciatic nerve stiffness between the symptomatic and asymptomatic limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative tendinopathy, on the other hand, represents a noninflammatory proliferative cell and matrix response with increases in type III collagen production, extracellular matrix disorganization, and cell death, which can manifest as increased tissue stiffness. 43 In studies of the axial spine, it was observed that in certain cases there was no notable variance in tissue stiffness within the trapezius muscle or sciatic nerve when comparing patients with pathology to healthy control participants. 22,23 However, several studies indicated that comparing side-to-side evaluations of Young's modulus or SWV in the same individual, between the symptomatic and asymptomatic side, will provide helpful diagnostic information, as noted in comparison of sciatic nerve stiffness between the symptomatic and asymptomatic limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the matrix architecture, matrix stiffness is also crucial in maintaining the tenogenic phenotype. Compared to the native tendon, culturing tendon cells in the plastic substrate led to a significant decrease in the SCX expression, whereas tendons mimicking substrate stiffness maintained a tenogenic phenotype. , Human mesenchymal stem cells (hMSCs) cultured on substrates with stiffness ranging from 0.1 to 10 MPa observed the increased tenogenic potential of hMSCs on the stiffness of 1 and 10 MPa with increased expression of SCX and type-I collagen . However, the previous in vitro models fail to account for the appropriate substrate stiffness and architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the importance of appropriate substrate stiffness and architecture in regulating cell phenotype. SCX is one of the primary markers for the tenogenic phenotype, and previous studies have demonstrated the importance of substrate stiffness and architecture in maintaining cell morphology and SCX expression. , Studies have found that tenocytes in anisotropic matrices exhibit an elongated cell morphology and have increased levels of SCX expression compared to the cells on isotropic matrix, while the loss of matrix anisotropy leads to decreased SCX expression. ,, Not only in tenocytes but tendon progenitor stem cells also cultured on an anisotropic matrix express increased levels of SCX compared to that of cells on an isotropic matrix . Along with the matrix architecture, matrix stiffness is also crucial in maintaining the tenogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate stiffness is one of the most common factors that stem cells sense in the ECM microenvironment. Previous researches suggested that substrate stiffness plays a pivotal role in the proliferation, migration and differentiation of stem cells ( Engler et al, 2006 ; Konar et al, 2022 ). In terms of tendon tissues, substrate stiffness has been suggested to affect the tenogenic differentiation of stem cells ( Islam et al, 2017 ).…”
Section: Applications Of Hydrogel/stem Cell Therapy In Tendon Repairmentioning
confidence: 99%